Analisis Pengaruh Flash Sale dan Tagline “Gratis Ongkir” Terhadap Keputusan Pembelian pada Shopee - Untari, Shabrina; Isyanto, Puji; Sumarni, Neni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the influence of flash sales and the tagline "free shipping" on purchasing decisions on Shopee. In this research the author uses quantitative research with an associative approach. The results of this research are that the flash sale variable and the tagline "free shipping" partially influence purchasing decisions in Karawang City and the flash sale variable and the tagline "free shipping" simultaneously influence purchasing decisions in Karawang City. Because of the strong encouragement from the flash sale offered by Shopee and the tagline "free shipping" on Shopee, it can lead to purchasing decisions among consumers who see it. This shows that the more Shopee flash sale programs and free shipping available on Shopee, the more purchasing decisions will increase.